On Making Humans Human: Engaging Affective, Cognitive, and Spiritual Dimensions within Instructional Design - Manubey, Johana; Sitompul, Nurmida Catherine (Journal of Pedagogy and Education Science, 2025)
This paper aims to illustrate how to integrate the cognitive, affective, and spiritual dimensions using the models developed by Buchanan and Taplin. Buchanan's model incorporates the three components into religious education, while Taplin's is secular. However, they have not yet integrated model stages into instructional design, especially instructional events. This research uses the document analysis method, a systematic document review procedure. Document analysis requires data analysis and interpretation to gain meaning, comprehension, and empirical information. This study's central questions are: How can instructional design use these three dimensions, especially in Gagne's nine learning events? Data extraction finds literature on merging these dimensions. Build a conceptual framework to explain how these three dimensions interact in instructional design. This study outlines integrating the three dimensions in instructional design utilizing Gagne's nine learning events. This study will allow teachers to plan learning with cognitive, emotional, and spiritual dimensions and change how people learn.